Ուրարտական պետության հարկային և իրավական համակարգերը - Սարգսյան, Դմիտրի («Զանգակ - 97»)
The Urartian State has a wide net of tax-collecting Organization leaded by the king. The cuneiform Urartian texts refer to several important officers who were busy with taxes - "the man of money", "the man of account". "senior herdsman", etc. Taxes were of different types - metals, livestock, agricultural products, armour and weapons, cloths. Since the Urartian State does not have written laws, all juridical decisions were conducted by the king himself, through his Orders and inscriptions. In the provinces the juridical power of the king was conducting by his officials - "man of the seal", "man of the palace", etc.
Keywords: Պատմություն; Իրավունք